Associations Between Screen Time and Mindfulness and Eating Behaviors Among Turkish School-Aged Children: A Cross-Sectional Study - İlayda Temizarabacı; Gizem Köse; Murat Baş; Ina Nehring (Children)
Background/Objectives: Increasing screen time in childhood has been suggested to impact physical health, eating behaviors, and well-being. This study investigated how screen time affects mindfulness, mindful eating, and diet quality in Turkish adolescents aged 9–12 years. Methods: One hundred thirty-seven participants completed surveys on anthropometry, screen time, the Godin Leisure-Time Exercise Questionnaire, the Mediterranean Diet Quality Index, the Mindful Eating Questionnaire for Children, and the Child and Adolescent Mindfulness Measure. Results: The average screen time was 4.43 ± 2.37 h/day. Significant negative correlations emerged between screen time and mindfulness (r = −0.471, p < 0.001), as well as between screen time and diet quality (r = −0.244, p < 0.05). A regression analysis revealed significant associations only for mindfulness (B = −0.158, p < 0.001) and age (B = 0.636, p = 0.002). Conclusions: Higher mindfulness and younger age correlated with lower screen time, suggesting mindfulness interventions in schools may reduce screen use.